An update on brivaracetam for the treatment of pediatric partial epilepsy. (24th July 2021) - Tulli, Eleonora; Di Cara, Giuseppe; Iapadre, Giulia; Striano, Pasquale; Verrotti, Alberto
ABSTRACT: Introduction : Brivaracetam (BRV) is an antiseizure medication (ASM), which has been approved as an adjunctive treatment in adults and pediatric patients aged four years and older with focal onset seizures. It is a second-generation levetiracetam (LEV) derivative, sharing the same mechanism of action, binding synaptic vesicles 2A (SV2A). BRV shows higher binding affinity and selectivity and higher brain permeability than LEV. Areas covered : This article reviews randomized controlled trials, retrospective and prospective studies published up to December 2020, searched in electronic databases MEDLINE, EMBASE and the Clinical Trial Database and provide an overview of efficacy, safety and tolerability of BRV in pediatric patients with partial epilepsy. Furthermore, the authors provide their expert opinion on the drug and give their future perspectives. Expert opinion : The analysis of the literature data has demonstrated the safety and efficacy of BRV in pediatric patients, with more evidence in children aged 4 to 16 years with an onset of focal seizures. However, a positive response was also achieved in patients affected by some encephalopathic epilepsies. Comparative efficacy studies between BRV and other ASMs, in addition to well-designed RCTs that include larger pediatric populations are needed to better define the role and potentiality of this ASM.